21st century communication : listening, speaking, and critical thinking. Teachers guide 4 - Lee, Christien, ....- (Boston : National Geographic Learning, 2017)
21st centruy Communication is a four-level series that uses powerful ideas from TED Talks to teach learners to think critically and communicate effectively. Through authentic models of effective communication, students build fluency in the listening and speaking skills needed to achieve academic and personal success.
Keywords: Communication skills : English